Status survey, distribution and habitat preferences of small carnivores in Parambikulam tiger reserve, Kerala - Sreehari R (Department of wild life sciences,College of Forestry, 2012)
A study was done at Parambikulam Tiger Reserve (PKTR) to understand the diversity, status, distribution and habitat preferences of the small carnivores at PKTR. The methodology used included the camera trapping, with 1,349camera-trap nights, day transects (242km) and night transects (344km), looking for direct as well as indirect evidences. The camera trap studies show that the 90% of the small carnivores captured in the camera traps belonged to three species of viverrids such as the Small Indian Civet (31.7%), Common Palm Civet (30%) and Brown Palm Civet (28.3%). The other small carnivores accounted for only 10% which includes, Stripe-necked Mongoose (3.3%), Smooth-coated Otter (1.7%), Nilgiri Marten (1.7%), Ruddy Mongoose (1.7%) and Leopard Cat (1.7%). The 242km of day transects also resulted in 15 sightings of five different species of small carnivores. They are Indian Grey Mongoose, Stripe-necked Mongoose, Brown Mongoose, Smooth-coated Otter and Common Palm Civet. The night spot-light survey transect of 344km on vehicle resulted in 36 sightings of recorded five species of small carnivores including Jungle Cat, Leopard Cat, Common Palm Civet, Brown Palm Civet and Small Indian Civet with an encounter rate of 1.06 animals/hr. A total of 88 incidence of indirect evidences of small carnivores were recorded from 242km transect walk. Abundance of small carnivores (scats/kilometer), with the civets (0.24) having the maximum abundance followed by mongoose (0.05), otters (0.04) and small cats (0.02) at the PKTR. Of the total 11 species of small carnivores recorded from PKTR, the sightings of Brown Mongoose, Ruddy Mongoose, Nilgiri Marten and Brown Palm Civet were the first record of this species from PKTR. Moreover, the Brown Mongoose and Ruddy Mongoose the present sightings were the second sighting records from Kerala, the earlier sightings being from Peerumedu and Chinnar WLS respectively.